AN INVESTIGATION ON THE INDONESIAN CULTURAL ASPECTS IN ENGLISH TEXTBOOKS FOR SENIOR HIGH SCHOOLPUBLISHED BY KEMENDIKBUD - syam, samsudin (Lingual Journal of Language and Culture, 2020)
Abstract Cultural understanding is the core of language acquisition because language and culture can not be seperated with language. Culture can be understand through media either electronic or manual such internet, magazine, textbooks etc. Textbook is one of the media used most people in school. In textbooks, there are many cultural aspects presented for students. Therefore, this study aimed at presenting the cultural aspects, describing the frequency of cultural aspects and Indonesian cultural aspects in English textbooks of  2013 curriculum and describing the level of quality of English textbooks in terms of intercultural awareness. This study employed a qualitative research design. The data are the cultural aspects and Indonesian cultural aspects in English textbooks of 2013 curriculum grade X, XI and XII. The textbook of these grades has not analyzed by the other researchers. The results show that English textbooks grade X, XI and XII contained 490 cultural aspects consisting of 232 products, 75 practices, 11 perspectives and 172 persons (Yuen:2001).While Indonesian cultural aspects contained 127 consisting of 64 cultural aspects on grade X, 34 on grade XI, and 29 on grade XII. From the results of the study, it can be concluded that the presentation of cultural aspects and Indonesian cultural aspects are not balanced and does not provide student to have intercultural awareness. And third English textbooks are equality to use in terms of basic cultural awareness. Whereas, advanced cultural awareness and  intercultural awareness leveldo not support students to have intercultural awareness. From the results above the authors of English textbooks should put the more cultural information explicitly Indonesian cultural aspects to enrich students cultural information.   Keyword: Indonesian Cultural Aspects, English Textbooks, Kemendikbud